The effects of L-carnitine supplementation on glycemic markers in adults: A systematic review and dose-response meta-analysis - Zamani, Mohammad; Pahlavani, Naseh; Nikbaf-Shandiz, Mahlagha; Rasaei, Niloufar; Ghaffarian-Ensaf, Rasool; Asbaghi, Omid; Shiraseb, Farideh; Rastgoo, Samira (Frontiers in Nutrition, 2023)
Hyperglycemia and insulin resistance are concerns today worldwide. Among the effective factors in glycemic control, some supplements, especially L-carnitine, have suggestions and possible effects. Therefore, it seems important to investigate its effect on glycemic markers. PubMed, Scopus, Web of Science, and the Cochrane databases for prospective studies on the effects of L-carnitine supplementation on glycemic markers were searched in October 2022. The inclusion criteria were adult participants and the oral L-carnitine supplementation must last for a minimum of seven days. The pooled weighted mean difference (WMD) was calculated using a random-effects model. We included the 41 RCTs (n=2900) with 44 effect sizes in this study. L-carnitine supplementation had a significant effect on fasting blood glucose (FBG) (mg/dl) in intervention, compared to a placebo [WMD= -3.22 mg/dl; 95%CI, -5.21 to -1.23; p=0.002; I2=88.6%, p<0.001], hemoglobin A1c (HbA1c) (%) [WMD= -0.27 %; 95%CI, -0.47 to -0.07; p=0.007; I2=90.1%, p<0.001] and homeostasis model assessment-estimate insulin resistance (HOMA-IR) [WMD= -0.73; 95%CI, -1.21 to -0.25; p=0.003; I2=98.2%, p<0.001] in intervention, compared to a placebo group, in the pooled analysis. L-carnitine supplementation had a reduced effect on baseline FBG ≥100 mg/dl, trial duration ≥ 12 weeks, intervention dose ≥2 g/day, overweight and obese participants (baseline BMI 25-29.9 and >30 kg/m2), and diabetic patients. Also, L-carnitine significantly impacted insulin (pmol/l), HOMA-IR (%), and HbA1c (%) in trial duration ≥12 weeks, intervention dose ≥2 g/day, and obese participants (baseline BMI >30 kg/m2). Moreover, had a reduced effect on HOMA-IR in diabetic patients, non-diabetic patients, and just diabetic patients for insulin, and HbA1c. There was a significant nonlinear relationship between the duration of intervention and changes in FBG, HbA1c, and HOMA-IR optimum duration consider 50 weeks. In addition, there was a significant nonlinear relationship between dose (≥2 g/day) and changes in insulin. Also, there was a significant linear relationship between the duration (weeks) (coefficients=-16.45, p=0.004) of intervention and changes in HbA1C. In conclusion, L-carnitine could improve the levels of FBG, HbA1c, and HOMA-IR.